2007
DOI: 10.1681/asn.2006070732
|View full text |Cite
|
Sign up to set email alerts
|

Mizoribine Corrects Defective Nephrin Biogenesis by Restoring Intracellular Energy Balance

Abstract: Proteins are modified and folded within the endoplasmic reticulum (ER). When the influx of proteins exceeds the capacity of the ER to handle the load, the ER is "stressed" and protein biogenesis is affected. We have previously shown that the induction of ER stress by ATP depletion in podocytes leads to mislocalization of nephrin and subsequent injury of podocytes. The aim of the present study was to determine whether ER stress is associated with proteinuria in vivo and whether the immunosuppressant mizoribine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 58 publications
(58 reference statements)
3
55
0
Order By: Relevance
“…puromycin aminonucleoside-induced nephrosis is associated with upregulation of podocyte GRP78. 16 In addition induction of familial focal segmental glomerulosclerosis (FSGS) in the mice (by expression of a-actinin-4K256E transgene in podocytes) results in expression of ER stress markers and proapoptotic proteins. 17 Moreover, markers of ER stress have been identified in the renal biopsy specimens from patients with various inflammatory and noninflammatory glomerulopathies.…”
Section: Translational Significancementioning
confidence: 99%
“…puromycin aminonucleoside-induced nephrosis is associated with upregulation of podocyte GRP78. 16 In addition induction of familial focal segmental glomerulosclerosis (FSGS) in the mice (by expression of a-actinin-4K256E transgene in podocytes) results in expression of ER stress markers and proapoptotic proteins. 17 Moreover, markers of ER stress have been identified in the renal biopsy specimens from patients with various inflammatory and noninflammatory glomerulopathies.…”
Section: Translational Significancementioning
confidence: 99%
“…[2][3][4] Previous studies have suggested a role for endoplasmic reticulum (ER) stress induction in podocytes using models of membranous nephropathy (Heymann nephritis) 5,6 and minimal-change nephrotic syndrome (puromycin nephrosis). 7 Moderate stress in the ER triggers many rescue responses, including an unfolded protein response and ER-associated degradation. 8 On the other hand, excessive or long-term exposure to ER stress induces impaired formation of the slit diaphragm complex and its associated lipid rafts as well as actin cytoskeleton abnormalities.…”
mentioning
confidence: 99%
“…7,8 In a previous study, we implicated ER stress in the development of the rodent model of minimalchange disease (MCD). 9 There are a number of studies suggesting that podocyte damage underlies the development of MCD; 10,11 however, the pathophysiological mechanisms of proteinuria have not been fully elucidated. In the rodent puromycin aminonucleoside (PAN) model of MCD, we showed upregulation of GRP78, a molecular chaperone stimulated by ER stress, in podocytes on days 4 and 5 at a heavy proteinuric state; we also showed that this GRP78 upregulation was associated with a change in the cellular localization of nephrin from the plasma membrane to the cytoplasm.…”
mentioning
confidence: 99%
“…In the rodent puromycin aminonucleoside (PAN) model of MCD, we showed upregulation of GRP78, a molecular chaperone stimulated by ER stress, in podocytes on days 4 and 5 at a heavy proteinuric state; we also showed that this GRP78 upregulation was associated with a change in the cellular localization of nephrin from the plasma membrane to the cytoplasm. 9 Nephrin is a transmembrane glycoprotein that is produced by podocytes and is responsible for the permselective barrier of the glomerulus. 12, 13 We previously determined that nephrin trafficking to the plasma membrane required N-glycosylation in the ER 14 and showed that a lack of ATP induced the hypoglycosylation of nephrin and its retention in the ER, which coincided with a strong induction of GRP78.…”
mentioning
confidence: 99%
See 1 more Smart Citation